Sistemas de Gestión del Aprendizaje potenciados por la Inteligencia Artificial. - Morocho Puculpala, Brandon Javier (2024)
This work responds to the needs of students in the fourth year of General Basic Education to have gamified tools to facilitate the learning process of the subject of Social Studies, for which different gamification tools were analyzed. It was determined that the most appropriate for this level and these contents is Blooket. Likewise, the curricular contents of the Social Studies subject of the fourth year of General Basic Education were reviewed. Unit 5, which focuses on the study of the natural regions of Ecuador, was selected. With these inputs, a proposal was designed to incorporate the Blooket tool in gamification processes in Social Studies for students in the fourth year of EGB, aligning the games with the specific pedagogical objectives. Finally, a manual for teachers of Blooket was developed, recommending the implementation of this proposal by teachers who teach the subject of Social Studies in the fourth year of EGB in the different educational institutions of the country to implement gamification as a practical, alternative, and innovative strategy in the classroom.